Internet of Things Implementation Analysis of Green Supply Chain Management in Companies - Habibatur Ridhah; Nini Sumarni; Tika Rahmayani Siregar; Fitria Fitria (Krigan: Journal of Management and Sharia Business, 2023)
Supply chain management is an important part of achieving company efficiency. The existence of globalization makes the transformation of technology in supply chains. The use of IoT in enterprise operations makes the company grow quickly and more effectively and efficiently. But this kind of performance makes there is more energy consumption. Environmental problems such as global warming and increasing air pollution arise, so many studies have suggested improving Supply Chain Management (SCM) with Green Supply Chain Management. In this study, we wanted to discuss "How ten companies in the world to do sustainability energy efficiency by using the GSCM (Green Supply Management) model so that it can reduce the risk of rising air pollution and global warming, and its correlation to Islamic Green Economics." This study uses the review literature method with a descriptive literature study model. Organized techniques were used to observe research studies from January 1, 2017, to April 2022, collected through various references. The results show that companies have widely applied the Green Supply Chain Management model. However, some companies have not implemented it because they do not understand the concept of GSCM. Even so, they have understood the concept of green, accompanied by caring for the environment and applying it in the company's operations. Manajemen rantai pasok merupakan bagian penting dalam mencapai efisiensi perusahaan. Adanya globalisasi membuat terjadinya transformasi teknologi dalam rantai pasok. Penggunaan Internet of Things (IoT) dalam operasi perusahaan membuat perusahaan tumbuh dengan cepat dan lebih efektif serta efisien. Namun, jenis kinerja seperti ini membuat konsumsi energi menjadi lebih tinggi. Masalah lingkungan seperti pemanasan global dan peningkatan polusi udara muncul, sehingga banyak penelitian yang telah menyarankan untuk meningkatkan Supply Chain Management, SCM dengan Green Supply Chain Management, GSC. Dalam penelitian ini, kami ingin membahas "Bagaimana sepuluh perusahaan di dunia menerapkan efisiensi energi berkelanjutan dengan menggunakan model GSCM (Green Supply Chain Management) agar dapat mengurangi risiko peningkatan polusi udara dan pemanasan global, serta korelasinya dengan Islamic Green Economics." Penelitian ini menggunakan metode tinjauan pustaka dengan model studi literatur deskriptif. Teknik-teknik terorganisir digunakan untuk mengamati) studi penelitian dari 1 Januari 2017 hingga April 2022, yang dikumpulkan melalui berbagai referensi. Hasil penelitian menunjukkan bahwa perusahaan-perusahaan telah secara luas menerapkan model Manajemen Rantai Pasokan Hijau. Namun, beberapa perusahaan belum menerapkannya karena mereka tidak memahami konsep GSCM. Meskipun demikian, mereka telah memahami konsep "hijau," yang didampingi dengan peduli terhadap lingkungan dan penerapannya dalam operasi perusahaan.